Environment Degradation and Rural Livelihood of Mulawarman Community in Indonesia - Agus Tianur; Pamerdi Giri Wiloso; Royke Roberth Siahanenia; Yohanes Budi Sulistioadi (Jurnal Manajemen Hutan Tropika, 2022)
This article aims to describe the livelihoods of communities around the mining area through cases in Mulawarman Village, Tenggarong Seberang District, Kutai Kartanegara Regency, East Kalimantan Province, Indonesia. This research uses a qualitative method with a case study approach. These findings show that the vegetation index value in Mulawarman Village degraded from 2014 (0.35) until 2019 (0.33). It shows forest degradation, which affects the livelihoods of rural communities that depend on agriculture or forestry. The leading cause of the decline in the vegetation index value is the expansion of coal mining activities. Indirectly, coal mining activities have limited the ability of the Mulawarman village community to access natural resources. Some residents of Mulawarman village have decided to sell agricultural land and move to other places. However, residents still survive to live in Mulawarman village by starting livestock and trading businesses to maintain their livelihoods.